Improving the Geodetic Infrastructure for Bathymetry and 3D Navigation in the German Exclusive Economic Zone of the North and Baltic Sea - Liebsch, Gunter; Schwabe, Joachim; Westfeld, Patrick; Förste, Christoph (The International Hydrographic Review, 2022)
Surveying and navigation became much easier, more accurate and operational thanks to the Global Positioning System. The use of this technology in height determination, bathymetry and 3-D navigation is not only limited by the reduced accuracy compared to the horizontal component. It supposes additional information about the geodetic height reference surface in order to leverage the full potential of this technology. The corresponding models, measurements and activities which are necessary to improve this part of the geodetic infrastructure are usually behind the curtain. This article emphasizes the need of a common cross-border geodetic infrastructure and the relevance of precise models of the height reference surface for GNSS-aided height determinations. The need of gravimetric surveys for the determination and improvement of these models is explained. Finally, it gives an overview about the gravimetric surveys which were carried out in the German Exclusive Zone of the North and Baltic Sea over more than one decade and provides some insight into practical aspects and challenges of this kind of surveys.